Appraisal of Retail Lending in DCCBs Based on Loans, NPAs, and Diversification - Gautam, Vandana (Indian Journal of Finance, 2017)
The biggest opportunity for the Indian banking system to grow and fulfill its natural obligations today is seen in the recent wave of consumerism and changing profile of the Indian consumer. Indian banks have changed their profile and have shifted to new operational strategies to face the challenges and volatility of the environment. The co-operative banks, which were promoted in India largely with a view to providing rural credit on easy terms and at low cost, are no exception to theÂ rule and have responded to the above banking challenges with full vigour by opting for diversification in high-yield areas of retail banking like the commercial banks. This paper made an attempt to study the impact of retail loaning on the working of District Central Cooperative Banks of Punjab by using secondary data. The paper was divided into three sections, the first section examined the extent of retail loan disbursement and NPAs in the DCCBs of Punjab ; the second section examined the affect of extent of diversification on the level of component wise retail loan disbursement and NPAs ; and the last section attempted to render certain valuable recommendations for improvement in the functioning of Cooperative banks.